Iron Triflate Salts as Highly Active Catalysts for the Solvent‐Free Oxidation of Cyclohexane. Issue 24 (15th April 2020) - Payard, Pierre‐Adrien; Zheng, Yu‐Ting; Zhou, Wen‐Juan; Khrouz, Lhoussain; Bonneviot, Laurent; Wischert, Raphael; Grimaud, Laurence; Pera‐Titus, Marc
Abstract : Among a series of iron salts, iron triflates revealed as highly active catalysts for the oxidation of cyclohexane by tert ‐butyl hydroperoxide into cyclohexanol and cyclohexanone with initial turnover frequencies higher than 10, 000 h – 1 . The structure of the iron complexes under the reaction conditions was studied by combining electron paramagnetic resonance (EPR) spectroscopy and DFT calculations. The coordination of the catalytic iron center readily evolved in the presence of the reaction products, leading ultimately to its deactivation. Iron and organic superoxo intermediates were identified as plausible active species allowing to rationalize the high activity of iron ligated by highly delocalized counter‐anions. Abstract : Among a series of iron salts, iron triflates revealed as highly active catalysts for the oxidation of cyclohexane by tert ‐butyl hydroperoxide into cyclohexanol and cyclohexanone with initial turnover frequencies higher than 10, 000 h – 1 . The coordination of the catalytic iron center readily evolved in the presence of the reaction products, ultimately deactivating it. Iron and organic superoxo intermediates were identified as plausible active species.